2017
DOI: 10.1590/1413-81232017224.28632016
|View full text |Cite
|
Sign up to set email alerts
|

Atenção primária à saúde e coordenação do cuidado nas regiões de saúde: perspectiva de gestores e usuários

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
83

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(126 citation statements)
references
References 25 publications
(29 reference statements)
1
42
0
83
Order By: Relevance
“…Other studies in these regions [2324] have confirmed the regional institution as the main service organizer in this area.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Other studies in these regions [2324] have confirmed the regional institution as the main service organizer in this area.…”
Section: Discussionmentioning
confidence: 52%
“…While making therapeutic itineraries with stroke patients in the same regions, Bousquat et al [23] reported similar results with no communication between services and professionals at different levels of assistance. They confirmed through interviews with patients in this clinical state that there are no mechanisms of continuity of care and care flow or vertical integration.…”
Section: Discussionmentioning
confidence: 98%
“…This research confirms findings of previous studies the very own regionalization process, which marks the low of coordination and planning actions, especially from the APS, [26][27][28] as well as other more recent studies that test the fragility of the articulation between the levels of care in regional networks, a recognized fact by managers themselves in another health region in São Paulo State. 29 It should be noted that the presence of the University Hospital in the region is a critical component for the patients' care who were affected by AVE. With all the obstacles in care present in the therapeutic itineraries analyzed in this study, the University Hospital of Traumas has allowed the access of the interviewed healthcare users who arrive at the emergency department, through formal or informal ways, from the two macro-regions that link the interstate health region.…”
Section: Discussionmentioning
confidence: 99%
“…At most, they have the support of the COSEMS, who are unable to effectively and regularly respond to the needs and difficulties of the small municipalities. This appears to be a relevant point in the debate on the difficulties in effectively implementing a basic health care network 45,46 .…”
Section: Second Note: the Mismatch Between The Policy's Formulation Amentioning
confidence: 99%